THE EFFECT OF IMPLEMENTATION OF PANCASILA STUDENTS’ PROFILE STRENGTHENING PROJECT IN SHAPING ENVIRONMENTAL CARE ATTITUDES FOR ELEMENTARY STUDENTS - Bagas Priatmojo; Muhammad Abiyyu Maulana; Yurniwati Yurniwati; Yofita Sari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Environmental care is a preventive measure against environmental damage and an effort to repair the damage that has occurred. The purpose of the research is to determine the effect of the implementation of the Pancasila Students’ Profile Strengthening Project on environmental care attitudes for 4th-grade elementary students in Benda District. The experimental research uses Pretest-Posttest Control Group Design with a quantitative research approach. Data collection instrument on environmental care attitudes uses questionnaires. The data are processed using the paired T-Test test after ensuring that the data is normal and homogeneous. The paired T-Test test results indicate t = 2.505 with pvalue = 0.023. Thus, it is concluded that there was a significant effect from the implementation of Pancasila Students’ Profile Strengthening Project learning on environmental care attitudes compared to conventional learning. In this paper, there is students’ improvement in waste management and environmental cleanliness. With the existence of the Pancasila Students’ Profile Strengthening Project, the teacher can make it alternative learning for students that is implemented at school in order to increase their environmental awareness.